Design of flight control system and autopilot for solar UAV : part 2 - Heng, Zeng Hui (2014)
This Final Year Project (FYP) aims to develop the software of the flight control system for a Solar-Powered Unmanned Aerial Vehicle (Solar UAV). The end goal will be to develop a system that is capable of supporting autonomous flight of the Solar UAW. Prior to the development of an offline simulation model using MATLAB and Simulink, key concepts in Flight Mechanics and Controls have to be reviewed. By applying these theories, such as the 6 Degree of Freedom Equations of Motion, state-space modelling and atmospheric disturbances, different model designs were constructed. Next, the lateral directional control block designed was validated by comparing the simulation results with the theoretical solutions. In contrary, the remaining models were not verified individually as they were assumed to be correct since it was constructed using blocksets obtained from the Simulink library. Instead, the overall offline simulation model was verified, using sample values adapted from “Flight Stability and Automatic Controls by Robert C. Nelson”, by comparing the simulated and literature results. This project also simulates the possible atmospheric disturbances that the UAV may experience during its flight, and its flight parameters responses before and after encountering the disturbance were studied. Hardware such as the Air Data System (ADS) for measuring and recording the necessary flight parameters were highlighted too. This project kick starts the development of the Solar UAV flight control system. Future works, such as the flight path optimization and hardware and software integration, were discussed in the report to suggest the next step moving forward from this FYP and eventually accomplishing the end objective.